Structure, Application, and Biochemistry of Microbial Keratinases - Li, Qingxin (Frontiers in Microbiology, 2021)
Keratinases belong to a class of proteases that are able to degrade polypeptides into amino acids. Microbial keratinases play important roles in turning keratin-containing wastes into value-added products by participating in the degradation of keratin. Keratin is found in human and animal hard tissues and its complicated structures make it resistant to degradation by common proteases and insoluble in water. Although many elements are involved in keratin degradation, keratinase is responsible for the cleavage of the peptides, making it attractive in pharmaceutical and feather industries. Keratinase can serve as an important tool to convert keratin-rich wastes such as feathers from poultry industry into diverse products applicable to many fields. Despite of some progress made in isolating keratinase-producing microorganisms, structural studies of keratinases and biochemical characterization of these enzymes, effort is still required to expand the application of keratinase in diverse fields by identifying more keratinases, understanding the mechanism of action and constructing more active enzymes through molecular biology and random mutagenesis. Herein this review covers structures, biochemistry, applications of microbial keratinases and strategies to improve its efficiency in keratin degradation.